Implementation of Humanist Learning Theory in Islamic Education Learning at SMA Negeri 19 Palembang - Diana, Miska Rossa; Harto, Kasinyo; Karolina, Asri (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
One of the main challenges of learning in the 21st century is how to develop learners' abilities holistically. In response to this challenge, SMA Negeri 19 Palembang applies humanistic learning theory in Islamic Religious Education (PAI) to encourage students' all-round development beyond mere academic achievement. This study aims to explore the application of the theory in Islamic Religious Education through the planning, implementation, and evaluation stages. Qualitative research methods involving observation, interviews, and document analysis were used to gain in-depth insights from educators and students. The results showed that the integration of the humanistic approach significantly increased student engagement through active learning, emotional engagement, and cooperative learning strategies. This approach not only improved academic understanding but also contributed to the development of social skills and character. This study implies that the application of humanistic approaches in education can create a more meaningful and effective learning experience and promote more holistic cognitive and affective growth